Forget-Them-Not creating accessible care through dementia-friendly public spaces as demonstrated with Marikina River Park - De Guzman, Mikhaela Beatrice G.
Dementia is a condition that not only directly affects an individual, but everyone close to them. The condition may cause a person to be aggressive, confused, and forgetful, among other characteristics. Because of this, a person with dementia may often isolate themselves and deteriorate at a faster rate. Currently, there is no cure for dementia and in a country like the Philippines that is known for their strong familial bonds, the idea of putting a relative with dementia in a senior home seems impractical and too expensive for them to afford. Given that exposure to nature, socialization, and physical activity can improve one’s quality of life and slower down cognitive decline, this study aims to give the few green public spaces the Philippines more purpose by making them dementia-friendly. This is through research not only on the unique traits present in Philippine culture, but most especially on the habits of a person affected with dementia and the elderly in general determined through surveying. This thesis aims to create a guide that would help designers create dementia-friendly public spaces suitable to Philippine culture. With dementia-friendly public parks, dementia care will be more accessible by allowing people with dementia to socialize, stay active, and in touch with nature either alone or with their loved ones.